Open soil surface brightness as a direct sign for soil recognition on LANDSAT images - I. Yu. Savin (Бюллетень Почвенного института им. В.В. Докучаева)
The variability of the brightness heterogeneities of the open chernozemic soil surface on LANDSAT images obtained in different seasons and different dates of survey were investigated. The brightness of the images (3 band) was unstable and considerably changes from one period of survey to another even within the one season of the year. Obtained results lead to the conclusion that during the automated recognition of soils on the satellite images the analysis of brightness of single image cannot serve as reliable basis for the digital soil mapping.